Genetic variation of Aedes aegypti mosquitoes across Thailand based on nuclear DNA sequences - Parimittr, Pimnapat; Chareonviriyaphap, Theeraphap; Bangs, Michael J.; Arunyawat, Uraiwan (Agriculture and Natural Resources, 2018)
The Aedes aegypti L. mosquito is the primary vector of dengue viruses in Thailand, where dengue disease is a major public health problem in both urban and rural areas. Understanding the genetic variation of Ae. aegypti populations can help to understand the distribution, population structure and gene flow of this species. Single nucleotide polymorphism (SNP) markers were used to analyze the genetic variation of 21 Ae. aegypti populations collected across six geographic locations in Thailand. Nuclear DNA sequences of four putative neutral fragments located on different chromosomes were examined. An average of 14 SNPs per kb was detected per population. Tajima's D statistical test showed no significant deviation from the neutral equilibrium model in the majority of populations, suggesting that the detected patterns of variation were under random mutation and genetic drift equilibrium. Relatively low genetic differentiation was detected between all mosquito populations.